Behavior of Saanen dairy goats in an enriched environment - Gomes, Karina Aurora Rodrigues; Valentim, Jean Kaique; Lemke, Sara Santana Ramos; Dallago, Gabriel Machado; Vargas, Ricardo Cruz; Paiva, Andre Luíz da Costa (Acta Scientiarum. Animal Sciences, 2018)
The objective of the present study was to evaluate the behavior of lactating Saanen dairy goats housed with or without the use of environmental enrichment technique. Twelve animals were split into two equal groups and assign to one of two treatments: stall with or without enrichment. Five objects were used to enrich the stalls: plastic PET bottles suspended and freely on the floor (both filled with corn as a visual and auditory stimuli), general cleaning brushes fixed to the wall of the stall, suspended tire, and a tree trunk for climbing. The behavior of the goats was observed during two hours for 10 consecutive days. The behaviors were recorded using focal-animal sampling method, observing each animal during 10-minute period. Descriptive statistics were calculated plotting the results in behavior frequency charts. Animals on both treatments showed similar behaviors frequencies for food intake and self-cleaning. However, a higher frequency of stereotyped behaviors was registered in the treatment without environmental enrichment. The highest frequency of interaction was observed for suspended tire, indicating animal’s preference for this object. In conclusion, animals on enriched environment show more different behaviors than animals in non-enriched environment and showed greater preference for some object over others.